Lessons learnt from 20 years of revenue sharing at Bwindi Impenetrable National Park, Uganda - Franks, Phil; Twinamatsiko, Medard (My University, 2017)
Bwindi Impenetrable National Park is one of the prime protected areas in Uganda, famous for its mountain gorilla families that have been habituated to allow gorilla tracking safaris. A revenue sharing (RS) scheme was established in 1995 through which 20 per cent of the park’s revenue was shared with park-adjacent communities. The objective of revenue sharing is to provide local communities with an incentive to support conservation, particularly when they might be adversely impacted for example through having their crops raided by wild animals. Revenue tends to be distributed as grants for projects. Uganda Wildlife Authority has national revenue-sharing guidelines applicable to all its parks and, building on these guidelines, is currently developing a formal revenue sharing regulation. During 2016 a learning evaluation based on 20 years of revenue sharing was carried out among communities surrounding Bwindi, with a view to strengthening the implementation of the revenue sharing and enabling it to become more effective and more equitable. The findings would also help inform the ongoing process of developing a national revenue sharing regulation. In addition, it was intended for the research to have global value, influencing conservation-related revenue-sharing policy and practice at other sites of great ape conservation within Africa and beyond. Although protected areas across the world are now far more likely to consider social and economic conditions in their surrounding communities alongside their biodiversity targets, many issues of equity and effectiveness in revenue sharing are still a long way from being resolved. As this study illustrates, there may be a number of different pathways through which a revenue-sharing scheme might deliver national/global conservation impact and local social impacts, but none of these can be taken for granted. An equity framework based on the three dimensions of recognition, procedure and distribution provides an opportunity for identifying improvements in revenue-sharing policy and practice.